2020
DOI: 10.1038/s41598-020-68296-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs as molecular markers of occupational grain dust exposure

Abstract: Dust from grain and feed production may cause adverse health effects in exposed workers. In this study we explored circulating miRNAs as potential biomarkers of occupational grain dust exposure. Twenty-two serum miRNAs were analyzed in 44 grain dust exposed workers and 22 controls. Exposed workers had significantly upregulated miR-18a-5p, miR-124-3p and miR-574-3p, and downregulated miR-19b-3p and miR-146a-5p, compared to controls. Putative target genes for the differentially expressed miRNAs were involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…On the other hand, we can reach different conclusions by analyzing the change in miR-574 expression (upregulation). The results of research conducted on a group of healthy individuals exposed to feed dust suggest that increased expression of miR-574 is a good predictor of such exposure [ 35 ]. Moreover, oncology studies also point to negative effects associated with increased miR-574 expression.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we can reach different conclusions by analyzing the change in miR-574 expression (upregulation). The results of research conducted on a group of healthy individuals exposed to feed dust suggest that increased expression of miR-574 is a good predictor of such exposure [ 35 ]. Moreover, oncology studies also point to negative effects associated with increased miR-574 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that a high concentration of cotinine in urine (as a measure of maternal smoking) was associated with miR-223 in maternal and cord blood. Although there is a lack of literature data on the effect of smoking on the expression of circulating miRNAs, the existing evidence have so far shown that air pollutants [ 57 ], working conditions [ 58 , 59 ] and metal exposure [ 60 ] might affect the regulation of circulating miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Other response markers of microbial exposure, such as increases serum amyloid A and C-reactive protein has been shown to be affected by the species composition in green houses 26 . We have previously shown differences in inflammatory markers and circulating miRNAs in blood of exposed workers compared to unexposed controls without finding any association with exposure measurements 27 , 28 . However, the complete assemblage of fungal species in the Norwegian grain elevators and animal feed mills has not been properly evaluated.…”
Section: Introductionmentioning
confidence: 85%